2006
DOI: 10.1103/physrevb.74.014104
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability ofZrSiO4under hydrostatic pressure

Abstract: We present the results of a combined experimental and theoretical investigation aimed to determine structural and equation-of-state parameters and phase stability thermodynamic boundaries of ZrSiO 4 polymorphs. Experimental unit-cell data have been obtained for a powdered sample in a diamond-anvil cell using energydispersive synchrotron x-ray diffraction with emphasis on the pressure range 0 -15 GPa. Static total-energy calculations have been performed within the density functional theory at local density and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 43 publications
8
31
1
Order By: Relevance
“…29 This reconstructive mechanism explains why the scheelite phases are metastable at ambient pressure and do not return to the zircon phase on release of pressure. 30,31 These results agree with our structural refinements, where it can be observed that the Cr-O and Tb-O distances do not change very much in both zircon and scheelite polymorphs, but there are remarkable changes in bond angles. These important changes appear to support the reconstructive model to explain this structural zircon-scheelite phase transition.…”
Section: A Structural Characterizationsupporting
confidence: 82%
“…29 This reconstructive mechanism explains why the scheelite phases are metastable at ambient pressure and do not return to the zircon phase on release of pressure. 30,31 These results agree with our structural refinements, where it can be observed that the Cr-O and Tb-O distances do not change very much in both zircon and scheelite polymorphs, but there are remarkable changes in bond angles. These important changes appear to support the reconstructive model to explain this structural zircon-scheelite phase transition.…”
Section: A Structural Characterizationsupporting
confidence: 82%
“…Indeed, there are many examples in the literature of ternary oxides (e.g. ZrSiO 4 , CaWO 4 ) [27,30] where bulk modulus differences of up to 20% are found depending on hydrostaticity despite being highly uncompressible materials. Usually, larger bulk moduli are systematically obtained with the less hydrostatic media [31] a fact that agrees with our findings for CuWO 4 .…”
Section: A X-ray Diffractionmentioning
confidence: 99%
“…Details of the computational parameters and the comparison with the results provided by the generalized gradient approximation (GGA) have been previously discussed [1]. In general, presure (p)-volume (V ) points and all our energetic profiles have been computed at zero temperature and neglecting zero point vibrational contributions.…”
Section: Computational Details and Mechanistic Modelsmentioning
confidence: 99%
“…According to the transformation matrices shown in Table I Table I, all these values can be compared with the zero pressure parameters of the corresponding conventional cells collected in Table I of Ref. [1].…”
Section: Accepted Manuscript IV Tetragonal Transitiomentioning
confidence: 99%
See 1 more Smart Citation